The Normal, Improving, and Productive Self: Unpacking Neoliberal Governmentality in Therapeutic Interactions. Issue 3 (3rd July 2019) - LaMarre, Andrea; Smoliak, Olga; Cool, Carmen; Kinavey, Hilary; Hardt, Laura
Abstract : Psychotherapy might be seen as a site of reproduction of neoliberal capitalist ideology. Unpacking therapeutic discourse affords the opportunity to explore neoliberalism in operation. We present a theoretical case for exploring neoliberalism in the therapeutic context. Specifically, we identify and illustrate three neoliberal discourses: the normal self, the improving self, and the productive self. We discuss how therapists might orient to these discourses and identify ways to challenge neoliberal ideology. Doing so will not dismantle power systems that yield oppression; however, it may help clients reclaim and negotiate preferred subjectivities within this system while also working toward broader social justice.